Factors Associated with Neonatal Asphyxia at Dr. M. Yunus Bengkulu Hospital 2024 - Adelia Utami Sebin; Desi Widiyanti; Epti Yorita; Nur Elly; Sri Yanniarti (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: This study aims to analyze the factors associated with the incidence of neonatal asphyxia in newborns at Dr. M. Yunus Bengkulu Regional General HospitalMethods: This analytical observational study employed a case-control design with a retrospective approach. The sample comprised 100 newborns, consisting of 50 asphyxia cases and 50 non-asphyxia controls. The case group was selected using simple random sampling via computer-generated randomization, while the control group was selected using systematic random sampling. Data were analyzed using the Chi-square test and binary logistic regression.Results: The results showed that there was a relationship between gestational age (p = 0.000), preeclampsia (p = 0.014), and birth weight (p = 0.000) with the incidence of neonatal asphyxia. The type of delivery was not significantly related (p>0.05). The most dominant variable was low birth weight with a value of Exp(B) = 4.653. Conclusion: Gestational age, preeclampsia, and birth weight are significantly associated with neonatal asphyxia, whereas the mode of delivery shows no correlation. Early detection and preventive measures are warranted, particularly for high-risk newborns such as those with low birth weight. AbstrakTujuan: Penelitian ini bertujuan menganalisis faktor-faktor yang berhubungan dengan kejadian asfiksia neonatorum pada bayi baru lahir di RSUD M. Yunus Bengkulu. Metode: Penelitian ini merupakan penelitian analitik observasional dengan desain case control menggunakan pendekatan retrospektif. Sampel berjumlah 100 responden yang terdiri dari 50 kasus asfiksia dan 50 non-asfiksia. Teknik pengambilan sampel kasus menggunakan metode simple random sampling berbantuan komputer (spin method), sedangkan sampel kontrol menggunakan systematic random sampling. Data dianalisis menggunakan uji chi-square dan regresi logistik biner.Hasil: Hasil penelitian menunjukan terdapat hubungan antara usia kehamilan (p =0.000), preeklampsia (p = 0.014), dan berat badan lahir (p = 0.000) dengan kejadian asfiksia neonatorum. Jenis persalinan tidak berhubungan secara bermakna (p>0.05). Variabel yang paling dominan adalah berat badan lahir rendah dengan nilai Exp(B) = 4.653.Kesimpulan: Faktor yang berpengaruh terhadap kejadian asfiksia neonatorum adalah usia kehamilan, preeklamsia, dan berat badan lahir, sedangkan jenis persalinan tidak berhubungan. Diperlukan peningkatan deteksi dini faktor risiko oleh tenaga kesehatan terutama pada bayi dengan BBLR.Kata Kunci: Asfiksia neonatorum; berat badan lahir; preeklamsia; usia kehamilan